ДИН ЖАНА УЛУТТУК БААЛУЛУКТАР - Мырзаибраимов, Самаган (Scientific Journal of Faculty of Theology, 2015)
In Kyrgyzstan, for solutions of formal problems related to the religious situation, important to determine the fundamental solution. The fundamental problems of different critiries in our life, religious value which based on nass (Qur‘an and Sunnah) and creating of systematic problems.